2018
DOI: 10.1111/cxo.12651
|View full text |Cite
|
Sign up to set email alerts
|

Vision in children with autism spectrum disorder: a critical review

Abstract: Autism spectrum disorder (ASD) is a common neurodevelopmental condition with approximately 1-2 per cent prevalence in the population. The condition has lifelong effects for the individual and family, and early intervention and management helps maximise quality of life and outcomes. Many studies of vision in ASD have attempted to link the behavioural and sensory deficits in ASD with underlying visual processing. From this work, it is clear that individuals with ASD 'see' and process the world differently, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 129 publications
3
49
1
Order By: Relevance
“…The variety of visual phenotypes reported in the literature may be due to the fact that ASD is a spectrum disorder, in which the severity and presentations of the symptoms vary over a very large range. Additionally, there have been many challenges in measuring visual function (including spatial acuity and contrast sensitivity) in this population, especially in children, because of wide variations in testing methods, sample sizes, selection of high-functioning participants, cooperativeness during visual testing, and social and communication difficulties [12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…The variety of visual phenotypes reported in the literature may be due to the fact that ASD is a spectrum disorder, in which the severity and presentations of the symptoms vary over a very large range. Additionally, there have been many challenges in measuring visual function (including spatial acuity and contrast sensitivity) in this population, especially in children, because of wide variations in testing methods, sample sizes, selection of high-functioning participants, cooperativeness during visual testing, and social and communication difficulties [12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…Simmons et al provided a comprehensive review of visual function in ASD with respect to the theories associated with ASD. More recently, Little and Bakroon have critically reviewed visual development and function in children with ASD. Recent systematic reviews have found there was a greater risk for children with ASD if they had a congenital hearing or visual impairment .…”
mentioning
confidence: 99%
“…In this work, we have investigated the retina of the VPA-induced model, since one of the hallmarks of ASD is hypersensitivity to sensory stimuli [15][16][17][18], and the retina is the primary sensory detector for vision. For example, ASD patients apparently perform better than usual in some visual tasks, and worse in others [19]. It has also been shown that certain types of visual stimulus, such as computer screen lights, capture the attention of individuals affected by ASD more than would be expected for neurotypical people [20].…”
mentioning
confidence: 99%